2012
DOI: 10.1038/oby.2012.180
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Can Lead to Resolution of Gastroesophageal Reflux Disease Symptoms: A Prospective Intervention Trial

Abstract: Objective-Weight gain is an important risk factor for gastroesophageal reflux disease (GERD); however, whether weight loss can lead to resolution of GERD symptoms is not clear. Our aim was to measure the impact of weight loss on GERD symptoms.Design and Methods-In a prospective cohort study at a tertiary referral center, overweight/ obese subjects (BMI 25-39.9 kg/m2) were enrolled in a structured weight loss program. Weight loss strategies included dietary modifications, increased physical activity and behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
(57 reference statements)
1
17
1
Order By: Relevance
“…In addition, the decreased BMI was associated with successful treatment with anti‐reflux medication. In a prospective cohort study of 332 obese adults enrolled in a weight loss program, a mean weight loss of 13 kg was observed, and there was significant decrease in the prevalence of GERD (15% vs 37%, P <.01) and the mean GERD symptom score (1.8 vs 5.5, P <.01) . Conversely, a relatively smaller study comprising obese patients (n=20) showed no significant changes in reflux symptoms after the loss of an average of 10.8 kg of weight, and another population‐based study (n=637) found no relation between weight loss and change in GERD symptoms …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the decreased BMI was associated with successful treatment with anti‐reflux medication. In a prospective cohort study of 332 obese adults enrolled in a weight loss program, a mean weight loss of 13 kg was observed, and there was significant decrease in the prevalence of GERD (15% vs 37%, P <.01) and the mean GERD symptom score (1.8 vs 5.5, P <.01) . Conversely, a relatively smaller study comprising obese patients (n=20) showed no significant changes in reflux symptoms after the loss of an average of 10.8 kg of weight, and another population‐based study (n=637) found no relation between weight loss and change in GERD symptoms …”
Section: Discussionmentioning
confidence: 96%
“…Thus, recent studies have investigated the association between changes in weight or WC and GERD, and have shown that weight gain or increase in WC is positively associated with the development of GERD symptoms or erosive esophagitis . However, there has been relatively little focus on the effect of weight loss or decrease in WC on improvement of GERD symptoms or erosive esophagitis . This study aimed to evaluate the association of weight loss or decrease in WC with GERD symptoms and erosive esophagitis in a large health‐screening cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The substantial weight loss associated with bariatric surgery has been shown to improve asthma with a 48%–100% improvement in symptoms and reduction in medication use (Juel, Ali, Nilas, & Ulrik, ); however, there is a potential threshold effect so that modest weight loss of 5%–10% may lead to clinical improvement (Lv, Xiao, & Ma, ). Similarly, modest weight loss of 5%–10% improves GERD (Singh et al., ) and liver function (Haufe et al., ). A study utilizing MRI scanning to examine the effects of weight loss on NAFLD has reported a reduction in liver fat from 18.3% to 13.6% ( p = .03), a relative reduction of 25% (Patel et al., ).…”
Section: Modest Weight Loss and Its Long‐term Maintenance: Benefits Amentioning
confidence: 98%
“…Overall, 81% of the subjects had reduction in GERD symptom scores and 65% had complete resolution. Furthermore, there was a significant correlation between percent weight loss and reduction in GERD symptom scores (26). In a study of contributing lifestyle measures, weight loss and head of the bed elevations were the two interventions with supporting evidence of benefit.…”
Section: Medical Managementmentioning
confidence: 94%